Effectiveness of publicity campaign encouraging earlier referral of hearing loss in adults. - King, R L (1987)
During 16,070 consultations in general practice 70 adults complained of difficulty with hearing. A simple poster displayed in the waiting areas together with an accompanying leaflet almost doubled the incidence of presentation of loss of hearing. Nevertheless, more than half of those complaining had failed to notice the prominently displayed personally relevant message, and the beneficial effect was lost almost as soon as the poster was removed.